2013
DOI: 10.1016/j.cell.2013.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of Molecular Subtype-Selective Vulnerabilities in Non-Small-Cell Lung Cancer

Abstract: SUMMARY Context-specific molecular vulnerabilities that arise during tumor evolution represent an attractive intervention target class. However, the frequency and diversity of somatic lesions detected among lung tumors can confound efforts to identify these targets. To confront this challenge, we have applied parallel screening of chemical and genetic perturbations within a panel of molecularly annotated NSCLC lines to identify intervention opportunities tightly linked to molecular response indicators predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(200 citation statements)
references
References 82 publications
11
188
0
1
Order By: Relevance
“…We subsequently analyzed NSCLC cell line models harboring a mutation in the gene encoding the inflammasome subunit NLRP3, which has previously been linked to hypersensitivity to RNAi-mediated FLIP depletion (20). In agreement with the literature, NLRP3 mutated HCC15 and H1373 cell lines were found to be highly sensitive to FLIP-depletion as determined by PARP cleavage ( Figure 3C).…”
Section: Radiation Induced Cell Death Issupporting
confidence: 83%
“…We subsequently analyzed NSCLC cell line models harboring a mutation in the gene encoding the inflammasome subunit NLRP3, which has previously been linked to hypersensitivity to RNAi-mediated FLIP depletion (20). In agreement with the literature, NLRP3 mutated HCC15 and H1373 cell lines were found to be highly sensitive to FLIP-depletion as determined by PARP cleavage ( Figure 3C).…”
Section: Radiation Induced Cell Death Issupporting
confidence: 83%
“…KRAS mutant NSCLC patients with concurrent LKB1 loss had a high number of metastatic sites at the time of diagnosis, and had a high incidence of extra-thoracic metastases [159]. Interestingly, concurrent mutations in KRAS and STK11 in human cancer cells resulted in susceptibility to the depletion of the coatomer complex I subunits [160], which are required for lysosomal maturation and CDC42-mediated transformation. More recently, an integrative analysis of genomic, transcriptomic, and proteomic data from early stage and chemo-refractory lung adenocarcinoma demonstrated that KRAS mutant lung cancer can be classified into three subgroups by cooccurring genetic alterations in STK11, TP53, and CDKN2A/B [161].…”
Section: Studies On Clinical Specimens and Clinical Trialsmentioning
confidence: 99%
“…Cox et al [14] provide a nice summary of KRAS synthetic lethal genes. However, two major challenges must be tackled before this method can be widely and effectively exploited: (1) synthetic interactions appear to be context dependent and tissue specific [66,67], therefore, an improved screening method is needed [14]; and (2) some identified targets such as the transcription factor GATA2 are themselves undruggable, therefore, it can be challenging in some situations to find appropriate targeting strategies [68].…”
Section: Taking Advantage Of Synthetic Lethalitymentioning
confidence: 99%